Incidência de infecções de sítio cirúrgico em cirurgias limpas em clínicas cirúrgicas de um hospital oncológico da Região Norte - SOARES, Rute Caroline Ramos (2022)
Health Care Related Infections (HAI) - formerly known by the terms nosocomial or nosocomial infection - are defined as adverse effects resulting from the patient care process in any health care service. Among the various types of HAIs, there is Surgical Site Infection (SSI), the third most prevalent type of infection in hospitals, which is a postoperative complication at the surgical procedure site, which is related to risk factors intrinsic to the patient, such as age and presence of comorbidities, and extrinsic ones, related to the procedure itself; if these factors are investigated and correctly adjusted, up to 70% of these infections could be avoided in Brazil. Cancer patients are more susceptible to these infections due to the immunological impairment to which they are exposed. This study aims to determine the incidence of surgical site infection in breast, cardiac and thoracic surgeries in an oncology hospital in the North Region, highlighting the main risk factors and etiological agents involved in the emergence of infections. This is an exploratory research with a quantitative, retrospective approach, carried out with 2,811 patients, in the period 2013-2020. Data collection was carried out in the files of the Hospital Infection Control Commission. The variables studied were: sex, age, notified clinic, etiologic agent and risk factors. Microsoft Office and SPSS software, version 20.0 were used for storage and statistical analysis. The study was approved by the Research Ethics Committee. The study found that 17 (0.6%) patients had infections, 13 (76.47%) were female and 4 (23.52%) were male. Escherichia coli and Staphylococcus Coagulase Negative (17.65%) were the most reported etiologic agents in SSI. The surgical wound was the main risk factor for SSI (33.33%). The observed SSI rate was low. These results will help to provide up-to-date knowledge about SSI-related risk factors to help with control interventions in hospitals.